The Relationship between Self-Awareness Behavior and Nurses' Ability to Implement Patient Safety - Titania Nur Rizkya; Supratman (Viva Medika, 2024)
The nurse's self-awareness behavior and ability play a very important role in patient safety. The nurse's behavior and ability play a very important role in patient safety performance. The purpose of this study was to determine the relationship between nurses' self-awareness behavior in carrying out patient safety at Dr. Moewardi Surakarta Hospital. This research is a quantitative research with a cross sectional design. The sample in this study amounted to 99 nurses. The study was conducted in January 2024 at Dr Moewardi Hospital Surakarta. The research instrument uses questionnaires developed by researchers. The results showed that the majority of respondents who had good self-awareness behavior also had good patient safety implementation as many as 71 people (80.7%). Meanwhile, respondents who had poor self-awareness behavior also had poor patient safety implementation as many as 6 people (2.6%) and obtained a significance value of 0.026. The results of the study can be concluded that there is a relationship between nurses' self-awareness behavior and patient safety at Dr. Moewardi Surakarta Hospital.